EXPLORING READING HABIT OF HIGH ACHIEVER STUDENTS AT UNIVERSITY LEVEL AT UNIVERSITY OF ISLAM MALANG - Latifatur Rohmah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Reading is fundamental skill for knowledge, character development, learning and academic achievements. In EFL context, reading in English language is beneficial for developing language proficiency. Reading is considered as habitual activity that involves the way in how much people read, how often people read and what do people read. However, many studies show that reading habit in Indonesia is still low. In this case, the current study aims to cover how is the students’ reading habit and what makes high achiever students different in terms of reading habit to the rest of the students. This study carried out using descriptive qualitative research method through semi structured interview. The data collected from 9 students of English department from University of Islam Malang through online with the use of WhatsApp voice note. The data analysed descriptively by analysing theme from interview excerpts to answer the research problems. The result indicates that high achiever students read more consistently and tend to gain information from various sources compared to low and mid achiever students. They also preferred to find their own material instead of being provided and did not affected by difficult reading content unlike low and mid achiever students. Moreover, high achiever students focus on self-development as their reason to read in developing skills and knowledge while low and mid achievers’ motivation mostly driven by assignment. In terms of receiving reading recommendation, low and mid achiever students mostly rely on friends and lecturers unlike high achievers who find additional recommendation in the internet.Key Words: Reading habit, high achievers.